Impact of Prewarming on Maintaining Perioperative Body Temperature: A Randomized Clinical Trial - Poveda, Vanessa de Brito; Gnatta, Juliana Rizzo; Lemos, Cassiane de Santana [UNESP]; Wonder, Amy Hagedorn; Nascimento, Ariane Souza do; Godoi, Michele Estevanatto Tose de; Possari, João Francisco; Ribeiro, Ulysses (Elsevier, 2025)
Purpose: To determine the prewarming effect on body temperature in the perioperative period of patients undergoing conventional abdominal surgery and the level of thermal comfort. Design: A randomized controlled clinical trial. Methods: A Brazilian oncology hospital located in São Paulo. A total of 99 patients aged 18 years or over undergoing elective conventional abdominal surgeries, with a minimum duration of 1 hour of anesthesia. The study was carried out from 2019 to 2021. Patients were randomized into 3 groups: prewarming with a blanket and cotton sheet (control; n = 33); prewarming with a forced-air warming system for 20 minutes (intervention 1; n = 33); prewarming with a forced-air warming system for 30 minutes (intervention 2; n = 33). Central temperature was measured by a zero-heat-flux temperature sensor every 20 minutes from the preoperative period until the surgery end time. The level of thermal comfort was determined through self-report during the preanesthetic and postanesthetic periods. Findings: There was a significant difference between the temperatures between the groups (P = .048), with evidence of greater benefit in maintaining the temperature in the group that received the prewarming intervention for 20 minutes. There was no significant difference between the percentage of temperatures below 36 °C among the groups (P = .135). Patients in the intervention groups were more comfortable during the postanesthetic recovery period than those in the control group (P = .048). Only 7 (8.24%) patients had postoperative chills (P = .399) and more than half of these incidents occurred in the control group (4; 13.3%). Conclusions: Prewarming for 20 minutes obtained the best results, showing the lowest average of temperature episodes below 36 °C during the intraoperative period and greater thermal comfort as reported by patients.
Keywords: accidental hypothermia; body temperature changes; hypothermia; perioperative care